2019
DOI: 10.3389/fphys.2019.01102
|View full text |Cite
|
Sign up to set email alerts
|

TLR2-Deficiency Promotes Prenatal LPS Exposure-Induced Offspring Hyperlipidemia

Abstract: Toll-like receptor 2 (TLR2), which recognizes several lipopeptides and transduces inflammatory signaling, promotes the pathogenesis of diet-induced dyslipidemia and obesity. TLR2-deficient mice were shown to have improved insulin sensitivity and reduced diet-induced metabolic syndrome. Previous studies demonstrated that prenatal lipopolysaccharide (LPS) exposure causes dyslipidemia accompanied by increased body weight and insulin resistance in offspring. To determine whether TLRs are involved in this complex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…On the other hand, the silencing of TLR2 resulted in a small and transient increase in TLR4 protein level. These observations are in line with previously published data, indicating functional and structural crosstalk between these receptors [69,70].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the silencing of TLR2 resulted in a small and transient increase in TLR4 protein level. These observations are in line with previously published data, indicating functional and structural crosstalk between these receptors [69,70].…”
Section: Discussionsupporting
confidence: 93%
“…C29 induced the upregulation of TLR4-encoding gene and protein levels, which may be at least partially responsible for the observed effect. A similar phenomenon was reported in mice deficient in TLR2 or TLR4 [ 69 , 70 ]. In contrast, Jang et al [ 35 ] found that the silencing of the TLR2 gene resulted in a substantial reduction in the TNF-α level.…”
Section: Discussionsupporting
confidence: 82%
“…However, we are yet to determine whether LPS damage to the gut affects the FXR and PXR pathways in enterocytes, thereby affecting the regulation of cholesterol by the gut microbiota. We observed that LPS translocation causes abnormal cholesterol metabolism and elevated serum LDL-C levels via TLR4-Myd88 in hepatocytes ( 106 109 ), which can be prevented by statins. Moreover, TLR4-Myd88 can activate both ERK and JNK signaling pathways in mice hepatocytes, thereby inhibiting CYP7A1 expression ( 132 ).…”
Section: Statins-related Potential Pathways Regulating Cholesterol Me...mentioning
confidence: 89%
“…Cao et al (2019) suggested more pronounce serum LDL-C changes in TLR2 knockout offspring mice and indicated that this may be due to a compensatory increase in TLR4 caused by TLR2 deficiency, manifested by an increased expression of TLR4 and Myd88 overactivity. Thus, the presence of LPS led to elevated serum LDL-C levels by activating TLR4 ( 106 ). Studies have discovered that the TLR4-Myd88 signaling pathway is related to lipid metabolism, as shown by the fact that the lipid-lowering effects of multiple lipid-lowering drugs are eliminated in Myd88 knockout mice ( 107 ).…”
Section: Points Of Contact Between Gut Microbiota and Cholesterol Met...mentioning
confidence: 99%
“…However, the interaction between TLR2 and LPS/TLR4 signaling pathways causes an opposing observation. Cao et al found that TLR2-deficient offspring of mice with prenatal LPS exposure had significantly more severe hyperlipidemia compared with WT offspring, with compensative upregulation of the TLR4/Myd88 signaling pathway in the adipose tissue [ 91 ].…”
Section: Gut Microbiota Derived Evs Participate In Inflammation Modul...mentioning
confidence: 99%